2019
DOI: 10.1039/c8re00345a
|View full text |Cite
|
Sign up to set email alerts
|

An autonomous microreactor platform for the rapid identification of kinetic models

Abstract: Rapid estimation of kinetic parameters with high precision is facilitated by automation combined with online Model-Based Design of Experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 68 publications
0
67
0
Order By: Relevance
“…More recently, Jensen has further developed a temperature scanning approach for flow reactors that exploits continuous spectroscopic monitoring where temperature and space velocity are changed simultaneously . Gavriilidis and coworkers have further developed this approach into an autonomous microreactor platform for rapid identification of kinetic models . A comparison of batch and ideal plug flow reactors equates distance or space velocity in flow with reaction time in batch.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Jensen has further developed a temperature scanning approach for flow reactors that exploits continuous spectroscopic monitoring where temperature and space velocity are changed simultaneously . Gavriilidis and coworkers have further developed this approach into an autonomous microreactor platform for rapid identification of kinetic models . A comparison of batch and ideal plug flow reactors equates distance or space velocity in flow with reaction time in batch.…”
Section: Figurementioning
confidence: 99%
“…[6] Gavriilidis and coworkers have further developed this approach into an autonomous microreactor platform for rapid identification of kinetic models. [7] A comparison of batch and ideal plug flow reactors equates distance or space velocity in flow with reaction time in batch. While great strides have been made in the past decade in the development of detailed, quantitative kinetic analysis in continuous flow reactor operation, [8,9] issues may still arise from unsteady-state behavior due to changing flow rates.…”
mentioning
confidence: 99%
“…16 While transient PFR studies have proven to be successful for generating kinetic data, recent work has shown that the design of the ramp transient experiment is crucial for producing highly informative data and that a good design is not intuitive, especially for experiments where multiple variables are ramped simultaneously. 20 When designing such an experiment the researcher must choose the initial value for all variables of interest (most commonly flowrate, feed concentration, temperature) and also choose the ramp rate for each variable. The simplest transient experiments to design are the single variable ramps, such as where only flowrate [11][12][13] or temperature 14,15,21 are ramped, while other variables are held constant.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge in designing ramp transient experiments is demonstrated in the literature, as trial and error is often required to obtain satisfactory experiment designs. 16,20 To address this challenge, in this paper a systematic strategy for designing ramp transient PFR experiments for both single variable ramps and multi variable ramps using model-based design of experiments (MBDoE) is presented and compared against traditionally designed experiments which have previously been published to demonstrate the value of this technique. 20 MBDoE is a method of designing experiments which uses the information already known about a system from its model structure and initial parameter estimates to design an experiment in an optimal way, most commonly with the objective of either distinguishing between two or more candidate models, 22 or for precisely estimating the parameter values in a single chosen model.…”
Section: Introductionmentioning
confidence: 99%
“…These transient data are currently not used for kinetic modeling because no specific simulation model was available to describe this stabilization behavior. It is reported in the literature that using transient data saves time and cost when there is a significant gap between the time required to reach steady state and the analysis time [28], which is the case in hydroprocessing.…”
Section: Introductionmentioning
confidence: 99%